(untitled) (Journal of Partial Differential Equations, 2020)
We consider steady compressible Navier-Stokes-Fourier system in a bounded two-dimensional domain with the pressure law p(ρ,ϑ)∼ρϑ+ρ ln^α(1+ρ). For the heat flux q∼-(1+ϑ^m)∇ϑ we show the existence of a weak solution provided α > max1,1/m, m > 0. This improves the recent result from [1].